2011
DOI: 10.1021/nl201124y
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Heterojunction Abruptness in VLS-Grown Semiconductor Nanowires via in situ Catalyst Alloying

Abstract: For advanced device applications, increasing the compositional abruptness of axial heterostructured and modulation doped nanowires is critical for optimizing performance. For nanowires grown from metal catalysts, the transition region width is dictated by the solute solubility within the catalyst. For example, as a result of the relatively high solubility of Si and Ge in liquid Au for vapor-liquid-solid (VLS) grown nanowires, the transition region width between an axial Si-Ge heterojunction is typically on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
114
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 29 publications
7
114
0
Order By: Relevance
“…Upon supersaturation of the liquid, the SiH x precipitated at the liquid−substrate interface, and the nanoneedles grew in a layerby-layer process. 45 As expected, the Si nanoneedles were successfully prepared on the surface of ZnO nanorods by PECVD. In our experimental conditions, the size of Au−Si droplet gets smaller and smaller owing to the loss and shrinkage that leads to gradual tapering nanoneedles taking place.…”
Section: Resultssupporting
confidence: 64%
“…Upon supersaturation of the liquid, the SiH x precipitated at the liquid−substrate interface, and the nanoneedles grew in a layerby-layer process. 45 As expected, the Si nanoneedles were successfully prepared on the surface of ZnO nanorods by PECVD. In our experimental conditions, the size of Au−Si droplet gets smaller and smaller owing to the loss and shrinkage that leads to gradual tapering nanoneedles taking place.…”
Section: Resultssupporting
confidence: 64%
“…Unfortunately, plenty of experiments had shown that the liquid alloy catalysts were fundamentally unable to form the atomically abrupt interfaces, especially for group IV nanowires (Si/Ge). 7,8 This is because the high solubility of growth species in the liquid alloy (for example, Si and Ge in Au−Si or Au−Ge catalyst droplet) result in a "reservoir effect" that creates a composition gradient at the heterostructure interfaces when switching between grown materials. 9,10 There was an alternative approach to reduce the reservoir effect by using the solid catalyst instead of liquid alloy droplet, which was called vapor−solid−solid (VSS) growth.…”
mentioning
confidence: 99%
“…Arrays of nanometer-sized clusters attract the interest of researchers due to the wide range of possible applications of such structures. In particular, the metal nanoparticles are used as a catalyst for growth of carbon nanotubes [1][2][3], nanowires of silicon and other semiconductors [4][5][6][7][8], as a catalyst for various chemical processes [9,10], in spectroscopy of surface enhanced Raman scattering [11,12], for medical purposes [13,14], in memory cells [15][16][17], in antireflection coatings of solar energy converters [18][19][20], in photonics and plasmonics [21][22][23].…”
Section: Introductionmentioning
confidence: 99%